Media Arts, Creative Economy Transformation, and Collaborative Urban Governance in Emerging Creative Cities: Evidence from Malang, Indonesia - Albaba, M Ziaelfikar; Aini, Asfa Agustina Nusba; Iswari, Hanif Rani; Ainun, Siti Nur; Meilani, Cindy (Badan Perencanaan Pembangunan Kota Malang, 2026)
The growing importance of creative economies has positioned Media Arts as a strategic driver of urban transformation, digital innovation, and sustainable competitiveness. However, existing creative city scholarship remains heavily concentrated on metropolitan cities in developed countries, while medium-sized cities in emerging economies, particularly in Southeast Asia, remain underexplored. This study examines the transformation of Malang City, Indonesia, into the first UNESCO Creative City of Media Arts in Southeast Asia by analyzing the integration of creative economy strategies, collaborative governance mechanisms, and Media Arts-based urban development. Using a qualitative descriptive case study approach, this research draws upon UNESCO dossiers, regional planning documents, policy reports, creative economy statistics, and relevant academic literature. The findings reveal that Malang’s transformation was supported by the synergistic interaction between cultural heritage, educational ecosystems, digital innovation, and collaborative governance institutionalized through the Culture–Talent–Technology (CTT) framework and the Hexahelix governance model. The study further demonstrates that Media Arts ecosystems contributed not only to economic growth and employment generation but also to cultural revitalization, urban branding, tourism development, and social inclusion. The findings contribute theoretically by extending creative city and collaborative governance literature through the proposed Media Arts-Based Urban Transformation Model for medium-sized cities in emerging economies. Practically, the study provides strategic insights for cities seeking to develop sustainable and globally competitive creative ecosystems through culturally grounded, innovation-oriented, and collaborative urban development strategies.